ASTP: MODEL PEMBELAJARAN BAHASA ASING BAGI MILITER - Nasution, A. Sayuti Anshari (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2009)
The United States Army during the Second World War stunned the education world with their foreign language teaching experience. Their program that is called “The Army Specialized Training Program” (ASTP) was able to successfully train many participants with a very high success rate. Dr. Hamada Ibrahim, a professor in foreign languages at Cairo University, Egypt, described the “ASTP” as the most immense and successful program of learning foreign language in the history. The US Army foreign language program encompasses the background for the emergence of this program, a general picture of the program, the teaching subjects as well as the teaching techniques. The success of the ASTP highlights the importance of well-designed curricula, immersive teaching methods, and the strategic alignment of language learning with practical needs. This historical example serves as a model for contemporary language education programs, suggesting that focused, purpose-driven training can yield exceptional outcomes. Additionally, the program’s effectiveness underscores the potential for adapting such methodologies in various fields, from diplomacy to global business, where multilingual competence is critical for success. This paper provides valuable insights for educators, policymakers, and linguists aiming to optimize foreign language acquisition in diverse contexts.